BAGAIMANA KAPABILITAS DINAMIS DAN MANAJEMEN PENGETAHUAN BERPENGARUH KEPADA KINERJA PERUSAHAAN? : SEBUAH BANGUNAN MODEL KONSEPTUAL - Kristinawati, Didin; Tjakraatmadja, Jann Hidajat (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 12 Nomor 2 Tahun 2018DO - 10.24843/MATRIK:JMBK.2018.v12.i02.p02, 2018)
ABSTRACT This study is aimed to develop a conceptual relationship between knowledge management and dynamic capabilities that will affect organizational performance. Knowledge is acquired, transferred, internalized, and combined through formal and informal processes in the SECI model will generate new knowledge for the organization. However, the knowledge repository per se is insufficient to boost performance. It needs a company's ability to create, integrate, modify and utilize its knowledge assets. The ability itself is the result of learning and practice within a company. Therefore, the factors that will create effective knowledge management process need to be facilitated by the company, which are related to learning culture, mistrust, and information technology support. In addition to the model, in the era of rapidly changing environmet, it is necessary to build members of organizations with t-shaped skill character namely expert in the knowledge specification as well as open-minded and capable to cooperate in cross-division. Keywords:   dynamic capability, knowledge management, learning habitat, performance, t-shaped skill